Cortical connections of auditory cortex in marmoset monkeys: lateral belt and parabelt regions - de la Mothe, Lisa A. (2012)
The current working model of primate auditory cortex is constructed from a number of studies of both New and Old World monkeys. It includes three levels of processing. A primary level, the core region, is surrounded both medially and laterally by a secondary belt region. A third level of processing, the parabelt region, is located lateral to the belt. The marmoset monkey (Callithrix jacchus jacchus) has become an important model system to study auditory processing, but its anatomical organization has not been fully established. In previous studies, we focused on the architecture and connections of the core and medial belt areas (de la Mothe et al., 2006a,b). In the current study the corticocortical connections of the lateral belt and parabelt were examined in the marmoset. Tracers were injected into both rostral and caudal portions of the lateral belt and parabelt. Both regions revealed topographic connections along the rostrocaudal axis, where caudal areas of injection had stronger connections with caudal areas, and rostral areas of injection with rostral areas. The lateral belt had strong connections with the core, belt and parabelt, whereas the parabelt had strong connections with the belt but not the core. Label in the core from injections in the parabelt was significantly reduced or absent, consistent with the idea that the parabelt relies mainly on the belt for its cortical input. In addition, the present and previous studies indicate hierarchical principles of anatomical organization in the marmoset that are consistent with those observed in other primates.